Domestic Coercive Control and Common Mental Disorders Among Women in Informal Settlements in Mumbai, India: A Cross-Sectional Survey. Issue 19 (October 2022) - Kanougiya, Suman; Daruwalla, Nayreen; Gram, Lu; Sivakami, Muthusamy; Osrin, David
Coercive control behaviors central to the abuse of power appear more frequent than other types of domestic violence, but little is known about its frequency, features, and consequences for women in India. We aimed to examine the prevalence of domestic coercive control and its association with physical, sexual, and emotional domestic violence in the preceding year and symptoms of depression, anxiety, and suicidal thinking. In a cross-sectional survey, we interviewed 4, 906 ever-married women aged 18-49 years living in urban informal settlements in Mumbai, India. We developed a 24-item scale of coercive control, assessed physical, sexual, and emotional violence using existing questions, and screened for symptoms of depression with the Patient Health Questionnaire (PHQ9), anxiety with the Generalized Anxiety Disorder (GAD7) questionnaire, and suicidal thinking with questions developed by the World Health Organization. Estimates involved univariable and multivariable logistic regression models and the prediction of marginal effects. The prevalence of domestic coercive control was 71%. In total, 23% of women reported domestic violence in the past 12 months (emotional 19%, physical 13%, sexual 4%). Adjusted models suggested that women exposed to controlling behavior had greater odds of surviving emotional (aOR 2.1; 95% CI 1.7, 2.7), physical (1.4; 1.0, 1.9), and sexual (1.8; 1.1, 3.0) domestic violence in the past 12 months; and higher odds of a positive screen for moderate or severe depression (1.7; 1.3, 2.2), anxiety (2.1; 1.3, 3.1), and suicidal thinking (1.7; 1.2, 2.3), and increased with each additional indicator of coercive control behavior. When women reported 24 indicators of coercive control, the adjusted predicted proportion with moderate or severe depressive symptoms was 60%, anxiety 42%, and suicidal thinking 17%. Inclusion of coercive control in programs to support domestic violence, would broaden our understanding of domestic abuse to resemble most victims experience and improve interventions.